Investigating the value of keeping options open for water infrastructure in the Lower Hunter, New South Wales. (February 2020) - Rust, Steven; Silberberg, Ben; Turner, Emma; Sharp, Basil
Abstract: Policy discussions around the world have increasingly focused on the need for resilient water and wastewater systems. The use of small-scale, 'incremental', measures that maintain substitutability in investment choices can improve a system's adaptability. Using past shifts/shocks, we estimate an option value for unforeseen events that can change the yield-demand balance for potable supply. For a hypothetical dam, we find avoided costs ranging from $11.1 m to $78.1 m for amounts of extra time ranging from one to ten years; and for a permanent desalination plant, the avoided costs ranged from $33.6 m up to $234.7 m for the same amounts of extra time. Highlights: Policy discussions have increasingly focused on a need for water resilience. We present a case study of the Hunter Water Corporation in Newcastle, Australia. We consider 'incremental' portfolios that can delay a new source by 1–10 years. Avoided cost ranges from $11.1 m up to $78.1 m for a hypothetical dam. Avoided cost ranges from $33.6 m up to $234.7 m for hypothetical desalination plant.